2007
DOI: 10.1016/j.ccr.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 Inhibits Mitochondrial Biogenesis and Cellular Respiration in VHL-Deficient Renal Cell Carcinoma by Repression of C-MYC Activity

Abstract: Many cancer cells are characterized by increased glycolysis and decreased respiration, even under aerobic conditions. The molecular mechanisms underlying this metabolic reprogramming are unclear. Here we show that hypoxia-inducible factor 1 (HIF-1) negatively regulates mitochondrial biogenesis and O(2) consumption in renal carcinoma cells lacking the von Hippel-Lindau tumor suppressor (VHL). HIF-1 mediates these effects by inhibiting C-MYC activity via two mechanisms. First, HIF-1 binds to and activates transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
709
4
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 788 publications
(755 citation statements)
references
References 65 publications
36
709
4
6
Order By: Relevance
“…Intriguingly, however, HIF and MYC are traditionally considered to have antagonistic effects in the hypoxic cell. Indeed, HIF was found to counteract MYC by various underlying mechanisms including the induction of MXI1, another MYC antagonist, competition with MYC for promoter binding or promoting its proteasomal degradation [45,46]. This paradox may reflect the different models studied so the biological relevance of the miR-210-promoted MYC functions in the regulation of HIF requires further clarification.…”
Section: Transcriptional Feedbackmentioning
confidence: 99%
“…Intriguingly, however, HIF and MYC are traditionally considered to have antagonistic effects in the hypoxic cell. Indeed, HIF was found to counteract MYC by various underlying mechanisms including the induction of MXI1, another MYC antagonist, competition with MYC for promoter binding or promoting its proteasomal degradation [45,46]. This paradox may reflect the different models studied so the biological relevance of the miR-210-promoted MYC functions in the regulation of HIF requires further clarification.…”
Section: Transcriptional Feedbackmentioning
confidence: 99%
“…29 Peroxisome proliferators-activated receptor g coactivator 1b is a transcription factor that is regulated by c-Myc and implicated in mitochondrial biogenesis. Study has shown that HIF-a overexpression in a pVHL-deficient renal carcinoma cell line inhibits PGC-1b expression, resulting in decreased mitochondrial DNA content, mitochondrial mass, and oxygen consumption.…”
Section: Hif-a Controls Mitochondrial Biogenesis By Inhibiting C-myc-mentioning
confidence: 99%
“…Study has shown that HIF-a overexpression in a pVHL-deficient renal carcinoma cell line inhibits PGC-1b expression, resulting in decreased mitochondrial DNA content, mitochondrial mass, and oxygen consumption. 29 Both HIF-1a and HIF-2a are involved in the transcriptional repression of PPARGC1B (encoding PGC-1b). In contrast to the direct role of HIF-1a in c-Myc target gene repression (Figure 2b), the HIF-a isoforms inhibit PPARGC1B expression in two indirect ways (Figure 4a).…”
Section: Hif-a Controls Mitochondrial Biogenesis By Inhibiting C-myc-mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it achieves high levels of ROS formation with increased apoptosis rate and severely suppresses cell proliferation and tumor growth. Interestingly, it has been reported that PGC1β knockout mice are protected from carcinogenesis (Bellafante et al ., 2014) and PGC1β expression can be regulated by c‐Myc, a key regulator for cell growth and proliferation (Soucek and Evan, 2010; Zhang et al ., 2007). This indicates that targeting PGC1β or PGC1β expression‐related pathways may be a new approach for antitumor drug development.…”
Section: Discussionmentioning
confidence: 99%